OUTCOMES OF SURGICAL TREATMENT FOR PERINEAL ENDOMETRIOSIS AT THE NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the outcomes of surgical treatment for perineal endometriosis (PE) at the National Hospital of Obstetrics and Gynecology.Methods: A descriptive study was conducted, collecting data from the medical records of patients diagnosed with PE who underwent surgery at the National Hospital of Obstetrics and Gynecology between January 2018 and August 2022. Inclusion criteria comprised patients diagnosed with PE who had undergone surgery, had histopathological confirmation of endometriosis, and whose records contained sufficient information. Patients with systemic diseases and/or histopathological results other than endometriosis were excluded. Pain severity was assessed using the Numerical Rating Scale (NRS, 0–10). Quality of life was evaluated using the SF-36 and classified as poor (0–25), moderate (26–75), or good (76–100).Results: A total of 48 patients were included in the analysis; the mean age was 31 ± 7.18 years (range, 20–43). The mean BMI was 19.74 ± 2.14 (range, 15.3–26.1), with the majority having a BMI of 18.5 to
Keywords: endometriosis; perineum; surgery; pelvic pain; NRS; SF-36.